Strategic alliances: an analysis of Catalan hospitals Alianzas estratégicas: un análisis de los hospitales catalanes - Merce Bernardo; Jaume Valls; Marti Casadesus (Pan American Health Organization, 2012)
OBJECTIVE: To analyze the strategic alliances that Catalan hospitals form with other health care entities and other types of institutions to foster technological and organizational innovation. METHODS: Qualitative case studies were conducted at a sample of 16 public hospitals in Catalonia, Spain. The sample was limited to three (Level 1-3) of Catalonia's four levels of hospitals (classified according to the complexity of the diagnoses and treatments they provide), but Level 4 hospitals were considered as part of the network in the analysis of the alliances. At each hospital, interviews were conducted with the manager, the medical director, and the service director, using a questionnaire that gathered information on strategic alliances with a focus on telemedicine. Qualitative data processing was applied to identify patterns of alliances between hospitals and other institutions. RESULTS: Catalan hospitals interact with other health care agents through three main types of associations: alliances with other hospitals (the most frequent type); alliances with primary care centers (reported mostly by Level 2 hospitals); and alliances with other institutions (e.g., local government, medical companies, and universities). Human resource-sharing (staff mobility) and training were reported most frequently as reasons for creating the alliances. CONCLUSIONS: Strategic alliances are formed between hospitals and other health care agents to help improve performance, competitiveness, and services provided to users. These results may help health care system managers promote strategic alliances as a means of optimizing system efficiency without reducing user satisfaction-a key challenge within the context of the current economic situation. OBJETIVO: Analizar las alianzas estratégicas que los hospitales catalanes forjan con otras entidades de atención de la salud y otros tipos de instituciones para fomentar la innovación tecnológica y de las organizaciones. MÉTODOS: Se condujeron estudios cualitativos de casos en una muestra de 16 ...